Occurrence of Toxoplasmosis in Baquba City, Diyala, Iraq - Mayada Nazar Jabbar AL-Khafaji; Sarra Raid Muhamed; Shaemaa Farhan Abdl-Kareem (Tikrit Journal of Pure Science)
The current study was conducted to determine the occurrence of toxoplasmosis in patients presented to Emergency Department, General, Educational Baquba Hospital, and Al-Batool Hospital in Baquba City, Diyala Province, Iraq, on the dependence of Serological Examinations from November 2018 to February 2019.